Measurement of Heart Rate, and Body Temperature Based on Android Platform - Musyahadah Arum Pertiwi; I Dewa Gede Hari Wisana; Triwiyanto Triwiyanto; Sasivimon Sukaphat (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2020)
Heart rate and body temperature can be used to determine the vital signs of humans. Heart rate and body temperature are two important parameters used by paramedics to determine the physical health condition and mental condition of a person. Because if your heart rate or body temperature is not normal then you need to make further efforts to avoid things that are not desirable. The purpose of this study is to design a heart rate and body temperature. In this study, the heart rate is detected using a finger sensor which placed on the finger. This sensor detects the heart rate pulses through infrared absorption of blood hemoglobin, and measure the body temperature using a DS18B20 temperature sensor which is placed axially. DS18B20 sensor works by converting temperature into digital data. The measurement results will be displayed on liquid crystal display (LCD) 2 x 16 and the data will be sent to android mobile phone via Bluetooth. After the comparision beetwen the desain and the standart, the error is 0.46% for beats per minutes (BPM) parameters and 0.31 degrees Celsius for temperature parameters.